Risk factors for the recurrence of instability after operative treatment of chronic lateral ankle instability: A systematic review - Ronny Lopes; Choon Chiet Hong; James Calder; Gino M. M. J. Kerkhoffs (Journal of Experimental Orthopaedics)
Abstract Purpose To identify, review and summarize risk factors for failure of lateral ankle ligament operative treatment for chronic lateral ankle instability (CLAI). Methods A Systematic review according to PRISMA guidelines was performed. In July 2023, a bibliographic search of the PubMed, Medline, CINAHL, Cochrane, and Embase databases was performed. Articles were included if they were quantitative studies published in English and reported risk factors for recurrence of instability. Results A total of 496 articles were identified using the search strategy, and nine articles were included. All were low‐quality cohort studies (level 3 or 4 evidence). These nine studies comprising 762 participants met the criteria for inclusion. Eighty‐nine patients (11%) had treatment failure as defined by recurrence of instability, with rates ranging from 5.7% to 28.5%. Six risk factors were divided into three categories: patient demographics (generalized joint laxity [GJL], high‐level sports activities and female sex), imaging features (varus hindfoot alignment), and surgical findings (poor quality of the remnant lateral ligaments, intraoperative syndesmosis widening). Conclusion The presence of risk factors such as GJL, high‐level sports activities, female sex, varus hindfoot alignment, poor ligament quality, and intraoperative syndesmosis widening should guide surgical strategy to reduce the risk of treatment failure in lateral ankle ligament repair for CLAI. Level of Evidence Level IV, systematic review.